2018
DOI: 10.1016/j.ceramint.2018.03.117
|View full text |Cite
|
Sign up to set email alerts
|

Annealing temperature influence on sol-gel processed zirconium oxide thin films for electronic applications

Abstract: A study of zirconium oxide (ZrO 2) thin films obtained by the non-alkoxide sol-gel method at different annealing temperatures, up to 450°C, is presented. Morphological, compositional, and optical characterizations of zirconia thin films show high transparency and high bandgap, besides homogeneous and non-porous surface. Metalinsulating-metal (MIM) devices were assembled from this zirconia material for electrical characterizations and have shown high electric resistivity and high specific capacitance. A study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…It has also been reported that the sol-gel method was used to prepare ultrathin ZrO 2 films for MOSFET [42,43]. For the preparation of thin films by the solution method, attention should be paid to the molar ratio of the precursor solution and the condition of the post-annealing treatment [44], which are crucial to the properties of the films. Generally speaking, the properties of the films prepared by the solution method are slightly worse than those of other traditional methods such as ALD.…”
Section: Sol-gel Methodsmentioning
confidence: 99%
“…It has also been reported that the sol-gel method was used to prepare ultrathin ZrO 2 films for MOSFET [42,43]. For the preparation of thin films by the solution method, attention should be paid to the molar ratio of the precursor solution and the condition of the post-annealing treatment [44], which are crucial to the properties of the films. Generally speaking, the properties of the films prepared by the solution method are slightly worse than those of other traditional methods such as ALD.…”
Section: Sol-gel Methodsmentioning
confidence: 99%
“…But these vacuum-based techniques are costly, energyintensive, require expensive starting material, and also time-consuming. This led to limited production and low throughput [11,12]. Compared with these vacuum-based deposition techniques, solution processing like the sol-gel method has become a popular method because of its low cost, easy controllability of chemical stoichiometry, low processing temperature, large-scale production, and its ability to produce chemically homogeneous and uniform films over large areas [13].…”
Section: Introductionmentioning
confidence: 99%
“…Thin film technologies have played a key role in the development of microelectronics, and now they play the same role in optoelectronics. Attractive materials for the application in optoelectronics include transition metal oxides films (TMOs) (TiO 2 , ZnO, HfO 2 , ZrO 2 , Ta 2 O 5 ) which, due to high optical energy band gaps, show good transmission properties in the Vis–NIR spectral range [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. The TiO 2 and ZnO films have sensor [ 9 , 10 , 11 , 12 ] and photocatalytic properties [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…TMOs are also used in integrated optics technologies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. TMO films can be produced using physical vapor deposition (PVD) methods, including e-beam evaporation [ 2 , 4 ], magnetron sputtering [ 7 , 8 , 9 , 13 , 23 , 29 ], pulse laser deposition PLD [ 30 ], or chemical methods, including chemical spray pyrolysis [ 12 ], atomic layer deposition (ALD) [ 5 , 10 , 14 , 17 ] and the sol–gel method [ 6 , 18 , 20 , 22 , 26 , 28 ]. PVD methods require utilization of specialized technological instruments including vacuum systems.…”
Section: Introductionmentioning
confidence: 99%